Does age at disease onset affect the clinical presentation and outcome in children with immunoglobulin A vasculitis? - Emine Nur Sunar Yayla,; Sevcan A. Bakkaloğlu, (Archives of Rheumatology, 2023)
Objectives: The study aimed to determine whether there is a relationship between the age at diagnosis and the clinical, laboratory, and prognostic features in pediatric immunoglobulin A vasculitis (IgAV) patients. Patients and methods: In this study, 539 pediatric IgAV patients (298 males, 241 females; mean age: 7.74±3.36 years; range, 1 to 17.8 years) were retrospectively evaluated between January 2005 and July 2020. The relationship between clinical findings and age at diagnosis was analyzed by univariate logistic regression analysis. Factors associated with renal involvement, steroid-dependent or refractory disease, and recurrence were examined. Results: The median age of diagnosis was 7.1 (1-17.8) years in all patients. At the time of admission, purpura, abdominal pain, and arthritis were the most common clinical findings. At the time of diagnosis, there was a positive association between age and purpura and an inverse association with the presence of arthritis. There were associations between renal involvement and age at diagnosis (odds ratio=1.22, 95% confidence interval 1.13-1.31, p<0.001), follow-up time (p<0.001), no history of previous infection (p<0.001), and presence of gastrointestinal (GI) involvement (p=0.003). Significant relationships were found between the age at diagnosis, follow-up time, GI involvement, renal involvement, scrotal involvement, the C-reactive protein value at the time of diagnosis, and the presence of steroid-dependent disease. An association was found between recurrence and GI involvement. All refractory patients had renal involvement. Age at diagnosis (p<0.001) and follow-up time (p<0.001) was found to be associated with refractory disease. Conclusion: Age at diagnosis and follow-up time may be associated with renal involvement and refractory and steroid-dependent disease in IgAV. In addition, there may be a relationship between steroid-dependent disease and renal, GI, and scrotal involvement and between GI involvement and recurrence.